$\begin{array}{l}\mathrm{for}\phantom{\rule{0.5em}{0ex}}i=1,2,\dots ,D\\ {\mathbit{t}}_{i}=\sum _{n=0}^{K-1}{d}_{i-1}^{*}\left[n\right]{\mathbit{X}}_{i-1}\left[n\right],{\mathbit{t}}_{i}-{\mathbit{t}}_{i}/{‖{\mathbf{t}}_{i}‖}_{2}\\ {d}_{i}\left[n\right]={\mathbit{t}}_{i}^{H}{\mathbit{X}}_{i-1}\left[n\right],n=0,1,\dots ,K-1\\ {\mathbit{X}}_{i}\left[n\right]={\mathbit{X}}_{i-1}\left[n\right]-{d}_{i}\left[n\right]{\mathbit{t}}_{i},n=0,1,\dots ,K-1\\ \mathrm{end}\\ {\epsilon }_{D}\left[n\right]={d}_{D}\left[n\right]\end{array}$ $\begin{array}{l}\mathrm{for}\phantom{\rule{0.5em}{0ex}}i=D-1,D-2,\dots ,0\\ {\omega }_{i+1}=\left\{\sum _{n=0}^{K-1}{d}_{i}^{*}\left[n\right]{\epsilon }_{i+1}^{*}\left[n\right]\right\}/\left\{\sum _{n=0}^{K-1}{\left|{\epsilon }_{i+1}^{*}\left[n\right]\right|}^{2}\right\}\\ {\epsilon }_{i}\left[n\right]={d}_{i}\left[n\right]-{\omega }_{i+1}{\epsilon }_{i+1}\left[n\right],n=0,1,\dots ,K-1\\ \mathrm{end}\\ {\mathbit{w}}_{0}^{\left(D\right)}=\sum _{i=1}^{D}{\left(-1\right)}^{i+1}\left\{{\prod }_{l=1}^{i}{\omega }_{l}\right\}{\mathbit{t}}_{i}\end{array}$